Reversing the Brain Drain of Human Capital through China Pakistan Economic Corridor - Dr. Fahad Khan Afridi; Dr. Muhammad Asif; Dr. Rashda Qazi; Dr. Waleed Afridi (Journal of Business & Tourism, 2021)
The research aims to assess the effect of CPEC on reversing the brain drain of Pakistan’s human capital. The research study is based on secondary data by using research articles, economic surveys, Bureau of Immigration and Overseas Employment etc. CPEC being a multibillion-dollar “Game Changer” can enhance the socio-commerce dimensions by reversing the brain drain of human capital of the country. It can only be possible by devising a viable strategic plan by the government for “Diaspora engagement policies”. The local and overseas Pakistanis should be involved in the projects only through their mobilization and engagement just like China and India did. Although, the present research article gives an insight to socio-economic impact of CPEC on Pakistan.